Chromitites of Teskuduk and Nurata Ophiolites (Southern Tien Shan Belt, Uzbekistan): Geochemical characteristics and implications of chromitite genesis - Donmez, Cahit; Aral, Zehra Deveci; Saka, Samet; Gunay, Kurtulus; Yildirim, Nail; Yildirim, Esra; Parlak, Osman (E Schweizerbartsche Verlagsbuchhandlung, 2025)
The Central Asian Orogenic Belt's ophiolites lack a full ophiolitic succession and instead occur as irregular fragments and slices in tectonic melanges and accretionary complexes. The Teskuduk and Northern Nurata ophiolites in Uzbekistan comprise extensively serpentinized mantle rocks that contain minor podiform chromitites, situated in the western area of the southern Tien Shan belt. Chromites in this region are found in a very limited area, and this study aims to determine the geochemical properties and formation environments of chromites by conducting geochemical studies on a limited number of recently discovered chromitites. In this context, mineral chemistry and platinum group element (PGE) geochemistry analyses were carried out on chromites. For Teskuduk chromitites, the Cr2O3, Al2O3, and TiO2 contents range from 53.2 to 55.7wt%, 11.1 to 12.7wt%, and 0.14 to 0.20 wt%, respectively, whereas for Nurata chromitites, the corresponding values range from 36.2 to 37.2 wt%, 23.1 to 30.2 wt%, and 0.10 to 0.30 wt%. The Teskuduk and Nurata chromitites contain a total average of 370 ppb and 117 ppb PGEs, respectively. They are classified as unfractionated chromitites, with low Pd/Ir ratios (0.03-0.20). These chromitite samples have chondrite-normalized PGE patterns that are identical to Cr-rich mantle-derived chromitites found in subduction-related ophiolites. Collectively, these data suggest that the Teskuduk ophiolites formed in a forearc setting, whereas the Nurata ophiolites evolved in a back-arc setting within the same oceanic branch.
Keywords: High-Cr; high-Al chromitite; platinum group elements (PGE); Teskuduk; Nurata; Uzbekistan; SSZ ophiolite